2021
DOI: 10.7150/jca.61445
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pretreatment albumin-to-alkaline phosphatase ratio in locally advanced laryngeal and hypopharyngeal cancer: Retrospective cohort study

Abstract: Background: This study was designed to assess the prognostic significance of pretreatment albumin-toalkaline phosphatase ratio (AAPR) in locally advanced laryngeal and hypopharyngeal cancer (LA-LHC). Materials and Methods:The clinical data of 341 patients with locally advanced laryngeal and hypopharyngeal cancer diagnosed between March 2007 and December 2018 were retrospectively collected and analyzed. The optimal cut-off value of AAPR for evaluating DFS was determined using the ROC curve, and 0.4912 was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“… 31 Another study also echoed that higher preoperative AAPR was one of the favorable predictors of DFS and OS in patients with locally advanced laryngeal and hypopharyngeal cancer. 10 Our study further strengthens the survival predictability of preoperative AAPR in the clinical practice for patients with LAOSCC.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“… 31 Another study also echoed that higher preoperative AAPR was one of the favorable predictors of DFS and OS in patients with locally advanced laryngeal and hypopharyngeal cancer. 10 Our study further strengthens the survival predictability of preoperative AAPR in the clinical practice for patients with LAOSCC.…”
Section: Discussionsupporting
confidence: 75%
“…28 Another study for patients with advanced NSCLC observed that an AAPR cut-off point of 0.36 was suitable for predicting OS. 29 For head and neck cancer, the optimal cut-off value is 0.51 for patients with LAOSCC as shown in our cohort, 0.4912 in the study for locally advanced laryngeal and hypopharyngeal cancer, 10 and 0.4876 for locally advanced NPC and 0.447 for metastatic NPC, respectively. 30,31 Generally, the optimal cut-off values can be determined by several statistical methods.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29]. However, there is limited evidence from large-scale general populations, making direct comparisons with our study challenging due to the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 93%